Handbook of linear partial differential equations for engineers and scientists - Poli︠a︡nin, A. D. (Andreĭ Dmitrievich); Nazaĭkinskiĭ, V. E. (CRC Press, Taylor & Francis Group, 2016)
Following in the footsteps of the authors' bestselling Handbook of Integral Equations and Handbook of Exact Solutions for Ordinary Differential Equations, this handbook presents brief formulations and exact solutions for more than 2,200 equations and problems in science and engineering.